2014
DOI: 10.1002/2014gc005425
|View full text |Cite
|
Sign up to set email alerts
|

A Cenozoic uplift history of Mexico and its surroundings from longitudinal river profiles

Abstract: Geodynamic models of mantle convection predict that Mexico and western North America share a history of dynamic support. We calculate admittance between gravity and topography, which indicates that the elastic thickness of the plate in Mexico is 11 km and in western North America it is 12 km. Admittance at wavelengths > 500 km in these regions suggests that topography is partly supported by subcrustal processes. These results corroborate estimates of residual topography from isostatic calculations and suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 109 publications
(261 reference statements)
4
39
0
1
Order By: Relevance
“…Thermochronometric and incision rate histories suggest that Cenozoic denudation of the Colorado and Rocky Mountains plateaus occurred in several stages (e.g., Flowers et al., ; Karlstrom et al., ; Winn et al., ). Staged Cenozoic uplift and denudation of North America is consistent with the history of sedimentary deposition observed along the northern and western margin of the Gulf of Mexico (Galloway et al., ; Stephenson et al., ). Feng et al.…”
Section: General Stratigraphic Constraintssupporting
confidence: 81%
See 1 more Smart Citation
“…Thermochronometric and incision rate histories suggest that Cenozoic denudation of the Colorado and Rocky Mountains plateaus occurred in several stages (e.g., Flowers et al., ; Karlstrom et al., ; Winn et al., ). Staged Cenozoic uplift and denudation of North America is consistent with the history of sedimentary deposition observed along the northern and western margin of the Gulf of Mexico (Galloway et al., ; Stephenson et al., ). Feng et al.…”
Section: General Stratigraphic Constraintssupporting
confidence: 81%
“…Ms = mouth of Mississippi; L = St. Lawrence; N = Nelson; Ma = Mackenzie; Y = Yukon; Cb = Columbia; Cd = Colorado. Drainage network is draped over dynamic topography that is calculated from long‐wavelength (i.e., <800 km) free‐air gravity anomalies assuming admittance, Z =25 mGal/km (GRACE mission database; Tapley et al., , Stephenson et al., ). Labeled circles indicate centers of major swells.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Roberts et al [2012a] developed a non-linear optimization scheme that permits substantial inventories of river profiles to be simultaneously inverted by varying uplift rate history as a function of both time and space. This general scheme has been successfully applied to different continents and suggests that the empirical stream-power formulation provides a practical basis by which patterns of regional uplift through space and time can be assessed [Roberts et al, 2012b;Czarnota et al, 2014;Paul et al, 2014;Wilson et al, 2014;Stephenson et al, 2014;Richards et al, 2016].…”
Section: Modeling Strategymentioning
confidence: 99%
“…The time span over which rivers respond to base-level changes, and thus the timescale taken to pass effects to the surrounding landscape is fundamentally determined by knickpoint migration rates (Whipple and Tucker, 1999;Whipple et al, 2000;Whipple, 2004;Wobus et al, 2006a). A number of studies have suggested that this process can take several million years (Merritts and Bull, 1989;Snyder et al, 2000;Whipple, 2001;Whittaker and Boulton, 2012;Stephenson et al, 2014). Consequently, this makes rivers ideal natural laboratories for evaluation of the landscape response to active faulting over Pliocene to Recent timescales.…”
Section: Existing Workmentioning
confidence: 99%